(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This expanded article provides an in-depth examination of morphological typology as one of the key frameworks in linguistic classification. The study offers a comprehensive comparison of isolating, agglutinative, fusional, and polysynthetic languages, emphasizing their structural, grammatical, and functional distinctions. It also evaluates the principles that shape morphological complexity, highlights universal tendencies, and discusses the significance of morphological typology for linguistic theory, language documentation, and comparative research. Examples from world languages are used to illustrate how different morphological strategies encode meaning. The extended analysis demonstrates the importance of morphology in understanding the cognitive and structural foundations of human language.